Cell Stress, Metabolic Reprogramming, and Cancer - Sergio Giannattasio (Frontiers Research Topics, 2018)
The present eBook presents one review, five mini-reviews, and an opinion article on the achievements and perspectives of studies on important aspects of cancer cell metabolic reprogramming whose mechanisms and regulation are still largely elusive. It also sheds light on certain novel functional components, which rewires cell metabolism in tumor transformation.